2015
DOI: 10.1002/2015gl065409
|View full text |Cite
|
Sign up to set email alerts
|

Submarine permafrost depth from ambient seismic noise

Abstract: Permafrost inundated since the last glacial maximum is degrading, potentially releasing trapped or stabilized greenhouse gases, but few observations of the depth of ice-bonded permafrost (IBP) below the seafloor exist for most of the arctic continental shelf. We use spectral ratios of the ambient vibration seismic wavefield, together with estimated shear wave velocity from the dispersion curves of surface waves, for estimating the thickness of the sediment overlying the IBP. Peaks in spectral ratios modeled fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 54 publications
0
21
0
2
Order By: Relevance
“…However, although the successful applications, the theoretical interpretation of the H/V function is still a matter of debate, mainly related to the unknown ambient vibration wavefield composition [ Lunedei and Malischewsky , ; Overduin et al ., ]. Three main physical interpretations of the H/V have been proposed in the literature [ Piña‐Flores et al ., ].…”
Section: Methods and Data Acquisitionmentioning
confidence: 99%
“…However, although the successful applications, the theoretical interpretation of the H/V function is still a matter of debate, mainly related to the unknown ambient vibration wavefield composition [ Lunedei and Malischewsky , ; Overduin et al ., ]. Three main physical interpretations of the H/V have been proposed in the literature [ Piña‐Flores et al ., ].…”
Section: Methods and Data Acquisitionmentioning
confidence: 99%
“…Lastly, arrays of multiple seismic stations could provide insights into the spatial variations of subsurface properties and alterations. Recent studies have demonstrated the opportunities and challenges for passive seismic monitoring of permafrost environments through horizontal‐to‐vertical spectral ratios (Abbott et al, ; Köhler & Weidle, ; Kula et al, ; Overduin et al, ). To date, using ambient noise for seismic interferometry has yet to be fully investigated for spatiotemporal monitoring of permafrost and active‐layer processes.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative geophysical methods like ground‐penetrating radar have proven to be effective at mapping taliks below freshwater grounded ice zones (Stevens et al, ) but are not suited for highly electrically conductive saltwater (Annan, ). While passive seismic has been recently used to map the depth to ice‐bearing subsea permafrost (Overduin et al, ), it is a technique still in development and not practical to achieve the desired spatial resolution of this study. Active seismic methods have been used to map the depth to deep ice‐bearing subsea permafrost offshore in the Laptev Sea (Hinz et al, ) but are less effective techniques in shallow coastal waters and are not sensitive to subtle changes of salt in the porewater of frozen sediment.…”
Section: Introductionmentioning
confidence: 99%